Current diagnosis and management of erectile dysfunction. Issue 10 (17th May 2019) - McMahon, Christopher G
Summary: Erectile dysfunction (ED) is a common male sexual dysfunction associated with a reduced quality of life for patients and their partners. ED is associated with increasing age, depression, obesity, lack of exercise, diabetes mellitus, hypertension, dyslipidaemia, cardiovascular disease and lower urinary tract symptoms related to benign prostatic hyperplasia. The evaluation of men with ED requires a full medical and personally and culturally sensitive sexual history, a focused clinical examination, fasting glucose levels, a fasting lipid profile and, in select cases, a total testosterone level and a prostate‐specific antigen test. Treatment of ED requires lifestyle modification, reduction of comorbid vascular risk factors, and treatment of organic or psychosexual dysfunction with either pharmacotherapy alone or in combination with psychosexual therapy. Between 60% and 65% of men with ED, including those with hypertension, diabetes mellitus, spinal cord injury and other comorbid medical conditions, can successfully complete intercourse in response to the phosphodiesterase type 5 inhibitors (PDE5i) sildenafil, tadalafil, vardenafil and avanafil. Patient‐administered intracorporal injection therapy using vasodilator drugs such as alprostadil is an effective treatment and is useful in men who fail to respond to oral pharmacological agents. Surgical treatment of ED with multicomponent inflatable penile implants is associated with high satisfaction rates. Penile arterial revascularisation and venous ligation surgery are associated with relatively poor outcome results in men with penile atherosclerotic disease or corporal veno‐occlusive dysfunction.